Legal Principles of Interference with Private Communication in the Process of Counterintelligence - KUDINOV, Serhiy S.; NAIDON, Juliana O.; PELIUKH, Oleg S.; ARTIUKHOVA, Nadiia O. (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
Counterintelligence is a special type of activity aimed at ensuring national security. The Ukrainian legislation regulates the rights of the authorized subjects of this activity in relation to intelligence, terrorist and other unlawful attacks of the special services of foreign states, including organizations, individual groups and persons that may adversely affect the national security of Ukraine. The purpose of this study is to identify the problems of interference in private communication during counterintelligence activities and to to private communication develop strategies for solving them, to explore the legal principles of interference with privacy, and in particular in the process of such activities. The results of the study will contribute to the development of the theory of national security, that is, to develop a procedure for intelligence and counterintelligence units to gain access to information transmitted between individuals in the process of direct communication or communication through connectivity.